2005
DOI: 10.1007/s11274-004-3907-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of cereals as basal medium for the formulation of alternative culture media for fungi

Abstract: The feasibility of developing alternative media to different culture media particularly potato dextrose agar was assessed using local cereal species as the basal media. Three cereal meal extracts -corn, sorghum and millet -were prepared, using them as substitute for the potato in potato dextrose agar. Potato dextrose agar (PDA) was the standard set up with which the performances of the formulated media were compared. Eight genera of fungi (Aspergillus niger, Fusarium moniliforme, Penicillium sp., Cercospora sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 7 publications
3
23
1
Order By: Relevance
“…Laleye (2002) reported a modification of Potato medium supplemented with cow dung, Soy milk and other growth factor for cultivation of fungi. Also, Adesemoye and Adedire (2005) studied the feasibility of developing alternative media to Potato Dextrose Agar (PDA) using local cereal species as a basal media. They observed that all the fungal species grew to some extent better on the formulated media in relation to the standard set up.…”
Section: Discussionmentioning
confidence: 99%
“…Laleye (2002) reported a modification of Potato medium supplemented with cow dung, Soy milk and other growth factor for cultivation of fungi. Also, Adesemoye and Adedire (2005) studied the feasibility of developing alternative media to Potato Dextrose Agar (PDA) using local cereal species as a basal media. They observed that all the fungal species grew to some extent better on the formulated media in relation to the standard set up.…”
Section: Discussionmentioning
confidence: 99%
“…Sterile pipettes were used to draw approximately 1 ml of 10 76 dilution aseptically onto one sterile centrimide agar plate and a hockey stick was used to spread the inoculum on the plate. The hockey stick was sterilized by dipping it in 70% (v/v) alcohol and passing through the Bunsen burner (Adesemoye & Adedire 2005). This was incubated aerobically for 18 -24 h in the incubator at 308C.…”
Section: Isolation and Characterization Of Pseudomonas Aeruginosamentioning
confidence: 99%
“…Corn meal has been generally considered a good substrate for fungal growth, has a high starch content (67.6~69.4%), and also contains other nutrients (Lee et al, 2008). Corn meal supported the high growth rate of a variety of fungal strains, such as Aspergillus niger , Fusarium moniliforme , Penicillium sp., Cercospora sp., Curvularia palesscens , Botryodiplopodia sp., Rhizopus sp., and Rhodotorula rubra (Adesemoye and Adedire, 2005). The growth of the 8 fungal species were noted to be approximately the same or occasionally better in corn meal medium as compared to those grown on PDA, a widely used but expensive commercial fungal medium.…”
Section: Discussionmentioning
confidence: 99%